1999
DOI: 10.1203/00006450-199911000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Prognosis Factors from the Clinical and Epidemiologic Analysis of a Registry of 229 Diamond-Blackfan Anemia Patients

Abstract: Diamond-Blackfan anemia (DBA) is a constitutional disease characterized by a specific maturation defect in cells of erythroid lineage. We have assembled a registry of 229 DBA patients, which includes 151 patients from France, 70 from Germany, and eight from other countries. Presence of malformations was significantly and independently associated with familial history of DBA, short stature at presentation (before any steroid therapy), and absence of hypotrophy at birth. Two hundred twenty-two patients were avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
1
2

Year Published

2006
2006
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 157 publications
(122 citation statements)
references
References 15 publications
5
114
1
2
Order By: Relevance
“…While this is still true, it is now clear that poor steroid sensitivity is common to all patients with RPS19 alterations. Their response to the first steroid course is 46% (42/91 patients whose data were available, two of them showing a partial response) compared with more than 70% of the overall DBA population [Ball et al, 1996;Willig et al, 1999b;Campagnoli et al, 2004;Lipton et al, 2006]. Over the last 10 years, clinical data from the main European and North American DBA registries have been published [Ball et al, 1996;Willig et al, 1999b;Campagnoli et al, 2004;Lipton et al, 2006].…”
Section: Genotype^phenotype Correlationmentioning
confidence: 99%
See 4 more Smart Citations
“…While this is still true, it is now clear that poor steroid sensitivity is common to all patients with RPS19 alterations. Their response to the first steroid course is 46% (42/91 patients whose data were available, two of them showing a partial response) compared with more than 70% of the overall DBA population [Ball et al, 1996;Willig et al, 1999b;Campagnoli et al, 2004;Lipton et al, 2006]. Over the last 10 years, clinical data from the main European and North American DBA registries have been published [Ball et al, 1996;Willig et al, 1999b;Campagnoli et al, 2004;Lipton et al, 2006].…”
Section: Genotype^phenotype Correlationmentioning
confidence: 99%
“…Their response to the first steroid course is 46% (42/91 patients whose data were available, two of them showing a partial response) compared with more than 70% of the overall DBA population [Ball et al, 1996;Willig et al, 1999b;Campagnoli et al, 2004;Lipton et al, 2006]. Over the last 10 years, clinical data from the main European and North American DBA registries have been published [Ball et al, 1996;Willig et al, 1999b;Campagnoli et al, 2004;Lipton et al, 2006]. Our review of these reports with data for over 800 DBA patients has shown that those with RPS19 mutations display a significantly lower sensitivity to steroids (po0.0001) and are significantly more likely to become transfusion dependent or require SCT (po0.0001) ( Table 2).…”
Section: Genotype^phenotype Correlationmentioning
confidence: 99%
See 3 more Smart Citations